Penerapan Manajemen Pendidikan dalam Mewujudkan Visi Sekolah - Salihibudayah Surahman (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
The purpose of this study is to examine the implementation of educational management in realizing the school’s vision (a study at SMP Negeri 2 Cina). The main problem of this research is how educational management is implemented in realizing the school’s vision. The sub-problems are: (1) How is educational management implemented at SMP Negeri 2 Cina, Bone (2) What is the contribution of the implementation of educational management in realizing the school’s vision at SMP Negeri 2 Cina, Bone. The results of the study indicate that the implementation of educational management in realizing the school’s vision is carried out through activities in each work unit so that they can be well organized toward the same goals. This includes allocating resources, planning and implementing programs, and directing groups of people to work together through planning, organizing, implementation, and supervision. These efforts facilitate the learning process, support the development of school activity programs, the preparation of plans and programs for quality improvement, and the evaluation of their implementation. The application of existing systems in accordance with the school’s expectations enables the learning process to run effectively and efficiently.